Data-driven exploration for pressure-induced superconductors using diamond anvil cell with boron-doped diamond electrodes and undoped diamond insulating layer. Issue 1 (2nd January 2020) - Matsumoto, Ryo; Hou, Zhufeng; Adachi, Shintaro; Nagao, Masanori; Yamamoto, Sayaka; Song, Peng; Kataoka, Noriyuki; de Castro, Pedro Baptista; Terashima, Kensei; Takeya, Hiroyuki; Tanaka, Hiromi; Yokoya, Takayoshi; et al.
ABSTRACT: Data-driven exploration for pressure-induced superconductors was performed based on the high-throughput first-principles screening of electronic band structures. In the screening conditions, we focused on the characteristics including a narrow band gap, flat band feature, and possibility of metallization under high pressure. The 27 promising compounds were screened out from the database of Atomwork for the candidates of new pressure-induced superconductors. Among the candidates, we actually synthesized three compounds in a single crystal, and all candidates exhibited the pressure-induced superconductivity. For the in-situ electrical transport measurements, we developed a novel configuration of diamond anvil cell with boron-doped diamond electrodes and an undoped diamond insulating layer. The discovered new pressure-induced superconductors via the data-driven approach and the developed diamond anvil cell were summarized in this paper.